Project team perception in green building projects implementation in Malaysia - Sharif, S.; Kamaruzzaman, S.N.; Pitt, M. (2014)
The purpose of this paper is to highlight Project Team Perception in Green Building Projects Implementation in Malaysia and its contribution to the success of Green Building Projects Implementation in Malaysia. The implementation of the green building projects depends on project team roles and responsibility in managing a Green Project. Project team is the core player in green building project implementation starting from planning, design, construction, supervision and maintenance. Project team roles and responsibility were investigated to have a significance degree of influence in green building implementation. Based on literature, 4 major factors have been identified as the major contributor to the Project Team Perception in Green Building Projects Implementation in Malaysia. The factors that are intended to be revealed such as Project Team Knowledge, Project Team Awareness, Project Team Experience and Ability Project Team adapting to change project management. This paper hopes to gives and creates a positive perception among project team in Green Building Projects Implementation in Malaysia.